DEVELOPMENT OF IDEAS OF CONTINUITY LABOR EDUCATION (1919 - 1934) - Antypin, Eugen (Educological discourse, 2018)
The article presents the results of theoretical synthesis the problem of continuity labor education of pre-schools and primary school aged children in a historical retrospective of 1919-1934. Investigation of this scientific problem will contribute the modern reforming processes in pre-school and primary school education. Nowadays we need to find ways to organize life-oriented study for pre-school and primary school aged children. We sure that historical and educational heritage will help to understand our opportunities and risks. Research was made on proven methodology concepts of modern Ukrainian historical and pedagogical science. Using the articles of educators published during 1919-1934, we were able to dwell on the main pedagogical ideas of the problem. System and narrative principles helps us to highlight the key ideas of continuity labor education of pre-school and primary school aged children. Author highlights the views of educational theorists and practice-men of definite period on labor education as a basis of children’s education that time. The period of 1919-1934 years, in the history of Ukrainian education, is the period of rising soviet system of education. But we understand this period like the period of transforming pre-school and primary education. This process was carried out with lots of creative ideas in labor education of pre-school and primary school aged children. The changes of development the basic ideas about the upbringing children of pre-school and primary school age in a context of practice-oriented labor education are characterized in the article.